Biosafety measures facing COVID-19 (Research, Society and Development, 2021)
Objective: To characterize the scientific production about biosafety measures used to fight COVID-19. Methods: This is an integrative review, carried out in April 2021 with the aim of promoting theoretical support based on the literature. The studies were selected from the LILACS, MEDLINE and SciELO databases, resulting in a sample of 15 articles. Results and Discussion: from the data analysis, two thematic categories emerged: I – “Biosafety measures adopted in the COVID-19 pandemic”; and II – “Impacts of COVID-19 on Biosafety and on the quality of life of health professionals”. Final considerations: Biosecurity measures are essential to contain the coronavirus, as it protects professionals, patients and the rest of the population. Despite the problems surrounding the topic, such as the lack of efficient public policies to contain the virus, professionals face high workloads to attend to the infected in the best possible way, even when there is a shortage of beds and adequate equipment.